2022
DOI: 10.1007/s12035-021-02696-0
|View full text |Cite
|
Sign up to set email alerts
|

Could SARS-CoV-2 Spike Protein Be Responsible for Long-COVID Syndrome?

Abstract: SARS-CoV-2 infects cells via its spike protein binding to its surface receptor on target cells and results in acute symptoms involving especially the lungs known as COVID-19. However, increasing evidence indicates that many patients develop a chronic condition characterized by fatigue and neuropsychiatric symptoms, termed long-COVID. Most of the vaccines produced so far for COVID-19 direct mammalian cells via either mRNA or an adenovirus vector to express the spike protein, or administer recombinant spike prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 234 publications
3
122
0
1
Order By: Relevance
“…In this regard, it has been proposed that the spike protein could damage the endothelium in an animal model, that it could disrupt an in vitro model of the blood–brain barrier (BBB), and that it can cross the BBB resulting in perivascular inflammation. These findings suggest an involvement of immune-related dysfunction in the development of post-COVID syndrome, and have led to the proposal of immunomodulatory treatments in conjunction with vaccination against COVID-19 in patients with long-term COVID-19 [ 41 , 42 ].…”
Section: Does the Spectrum Of The Autoimmune/inflammatory Syndrome Ex...mentioning
confidence: 99%
“…In this regard, it has been proposed that the spike protein could damage the endothelium in an animal model, that it could disrupt an in vitro model of the blood–brain barrier (BBB), and that it can cross the BBB resulting in perivascular inflammation. These findings suggest an involvement of immune-related dysfunction in the development of post-COVID syndrome, and have led to the proposal of immunomodulatory treatments in conjunction with vaccination against COVID-19 in patients with long-term COVID-19 [ 41 , 42 ].…”
Section: Does the Spectrum Of The Autoimmune/inflammatory Syndrome Ex...mentioning
confidence: 99%
“…Changes in taste and smell, headache, dizziness, coordination difficulties, memory loss, anxiety, and insomnia are also found. [ 121 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that pericytes are found in other organs such as brain, eye, skeletal muscle, and kidney suggest that the circulating S protein could cause damage to these organs [ 11 , 17 , 18 ]. The impact of the S protein on the brain has determined that it can disrupt the blood–brain barrier and cause perivascular inflammation [ 7–9 ]. Pathological consequences of the circulating S protein on pericytes in other organ systems remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that the S protein can cause detrimental effects in COVID-19 patients independent of infection could partially explain the long-term health issues. A previous study demonstrated that the S protein could damage the endothelium and disrupt the blood–brain ba[rrier resulting in perivascular inflammation [ 7–9 ]. Other actions of the S protein include direct stimulation of peripheral nerves, release of inflammatory factors, and stimulation of vasoactive mediators such as platelet-activating factor (PAF) [ 2 , 7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation